Development of Animated Learning Video Media Subtheme 2: Interrelationship Among Living Organisms - Syafi’ah, Rohmatus; Sari, Dwi Yulia (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract: The results of observations at SDN 1 Bono show that students like interesting audio and visuals, but teachers are lacking in utilizing the media. This study aims to provide information about the validity of learning video media, teacher and student response data about learning video media for food webs for Class V SDN 1 Bono Tulungagung. Video media has been developed in the form of animations that can be used on food chains and food web material. The ADDIE model was used as a development method in the research. The research trial subjects are material experts, media experts, fifth-grade students of SDN 1 Bono, and fifth-grade teachers of SDN 1 Bono. Questionnaires were used as a data collection technique to determine the responses of media and material experts, students, and teachers. Likert scale was used as a data analysis technique. The results showed that, in the limited trial and field trial, the learning video media for food webs were included in the very feasible criteria and based on the results of the teacher and student response questionnaires, it can be said that the media is practical to be applied.